Epidemiology of occupational dermatoses associated with personal protective equipment use in the COVID-19 pandemic: Risk factors and mitigation strategies for frontline health care workersCapsule Summary - Wen Yang Benjamin Ho, MBBS, MRCP, MMed; Llewelyn Yi Chang Tan, MBChB, MRCP; Xiahong Zhao, BSc (Hons); Dingyuan Wang, MBBS, MRCP; Hua Liang Joel Lim, MBBS, MRCP, MMed (Elsevier, 2022)
Background: Personal protective equipment (PPE)-related occupational dermatosis (PROD) represents a significant occupational burden to health care workers (HCWs), and understanding its epidemiology is imperative in formulating mitigation strategies. Objectives: To determine the prevalence of PROD in HCWs, characterize its manifestations, identify its risk factors, and evaluate behavioral modifications of HCW. Methods: A cross-sectional study using an online questionnaire was conducted from July to September 2020. HCWs who had direct contact with COVID-19 patients for a minimum of 2 weeks cumulatively were invited to participate. Results: The prevalence of PROD among 416 valid respondents was 73.8% (307/416), with face masks being the most common cause (93.8% [n = 288]). The most common PROD associated with face masks, protective eyewear, hairnets, gowns, and gloves were acne (71.5% [206/288]), pressure-related injuries (70.7% [99/140]), scalp itch (53.3% [16/30]), itch/rash (78.8% [26/33]), and xerosis (75.0% [27/36]), respectively. Exposure to PPE beyond an hour increased the odds of PROD by 4.8-fold. The majority of HCWs made behavioral modifications to mitigate PROD. Conclusions: We underscore evidence-based recommendations for HCWs to be (1) scheduled hourly breaks from PPE wear, (2) fitted to various PPE models, (3) screened for preexisting dermatoses before deployment, and (4) educated on mitigation strategies and avenues for help should they encounter PROD.